OPINION OF ATHLETES OF THE NEED REALIZATION OF PSYCHOLOGICAL PREPARATION IN FOOTBALL CLUBS OF VOJVODINA - Petar Kojić; Radovan Čokorilo (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
With the development of sport in the modern economy, the sciences and disciplines of the sport, there IS a need for the interdisciplinary study of sport and as a subject of study and attention of the scientific community now seen psychological preparation of athletes. However, the advantages and importance of psychological preparation of athletes in our environment, through various causes, are still not sufficiently recognized. With the aim of determining the need for the implementation of the psychological preparation of athletes in football clubs in Vojvodina was conducted empirical research (primarily explorative character) on a sample of 204 athletes from 10 clubs from the region of Vojvodina, who are competing in different levels of competition, from the highest to the lowest. This study was conducted descriptive research methods, interviewing techniques and collected data were analyzed using the chi square test theoretical frequency distribution and the C coefficient of contingency. The main results are related to the fact that the players interviewed expressed the need for the implementation of psychological preparation, psychological preparation to be done in preparation and competition period and that it is equally necessary for all and not a privilege of elite athletes. This research, we have concluded that the opinion that the athlete and the coach need psychological preparation and the trainer that I have a positive attitude towards the introduction of psychological preparation for the club. The results that we have obtained can be used to create a sports policy in terms of the introduction of psychological preparation in football clubs in the practice of Vojvodina and the diversion of sports public on the importance of psychological preparation of athletes in modern sport.